2015
DOI: 10.1016/j.sbspro.2015.06.276
|View full text |Cite
|
Sign up to set email alerts
|

Upper Echelon Theory Revisited: The Relationship between CEO Personal Characteristics and Financial Leverage Decision

Abstract: From the upper echelons perspective, we investigate the financial leverage decision of publicly listed companies in Bursa Malaysia for the period from 2002 to 2011. Using pooled OLS and fixed-effect regressions, we examine the impacts of CEO personal characteristics on financial leverage. Our measures of CEO personal characteristics such as CEO overconfidence based on CEO profile photo, CEO age, and CEO prior experience are significantly and negatively related to leverage. However, CEO education level and CEO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
31

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 46 publications
2
34
0
31
Order By: Relevance
“…Another demographic factor that could influence the firm performance is the director's age, as discovered by Amran, Yusof, Ishak, and Aripin (2014). Ting, Azizan, and Kweh (2015) found that younger CEOs are more likely to be aggressive and risk-taking. While Cline & Yore (2016) found that the age of S&P firm CEOs were negatively related to firm value and performance.…”
Section: Introductionmentioning
confidence: 98%
“…Another demographic factor that could influence the firm performance is the director's age, as discovered by Amran, Yusof, Ishak, and Aripin (2014). Ting, Azizan, and Kweh (2015) found that younger CEOs are more likely to be aggressive and risk-taking. While Cline & Yore (2016) found that the age of S&P firm CEOs were negatively related to firm value and performance.…”
Section: Introductionmentioning
confidence: 98%
“…A Teoria dos Escalões Superiores (do inglês Upper Echelon Theory), introduzida originalmente por Hambrick e Mason (1984) menciona que as características cognitivas e demográficas influenciam na estratégia adotada pelos CEO's ou pelas equipes de gestão e, assim, nos resultados organizacionais e nos níveis de desempenho (Hambrick & Mason, 1984). A TES sugere que quanto mais complexa uma decisão, por exemplo, medidas estratégicas, mais relevantes se tornam as características cognitivas e demográficas dos tomadores de decisões, tais como a idade e o tempo no cargo (Ting et al, 2015). Isso porque as equipes de gestão são caracterizadas pela racionalidade limitada e tomada de decisão com base no seu cognitivo e social (Ting et al, 2015).…”
Section: Teoria Dos Escalões Superiores -Tesunclassified
“…A TES sugere que quanto mais complexa uma decisão, por exemplo, medidas estratégicas, mais relevantes se tornam as características cognitivas e demográficas dos tomadores de decisões, tais como a idade e o tempo no cargo (Ting et al, 2015). Isso porque as equipes de gestão são caracterizadas pela racionalidade limitada e tomada de decisão com base no seu cognitivo e social (Ting et al, 2015).…”
Section: Teoria Dos Escalões Superiores -Tesunclassified
See 2 more Smart Citations